Tane's War & Shearing Identity: Envisioning New Zealand's Queer Past - Weir, Brendan (Auckland University of Technology, 2013)
This thesis explores whether a primarily minority-focused (homosexual) narrative can remain accessible and meaningful to a majority (heterosexual) audience. Through the perspective of Queer Theory, and through my own authorial paradigm as a gay artist, I examine the plausibility of gay characters and heroes to a mainstream audience and consider to what extent they should remain recognisable through the lens of mainstream social and cultural experience. The thesis is comprised of two elements; Tane’s War, the creative-practice-as-research component of the Master of Creative Writing degree and Shearing Identity, an exegesis critically reflecting upon the creative work. The exegesis is presented in two parts; a foreword discussing the form of the creative work (which is presented before the screenplay) and a critical analysis of my creative practice (presented after the screenplay). Tane’s War is presented as a screenplay for reading, a format which uses many traditional conventions of the screenplay but incorporates additional descriptive elements to allow any reader (not just those familiar with the screen-industry) a full understanding of character, structure and voice. Tane’s War is set in 1950s rural New Zealand and on France's Western-front during the Great War. It explores themes of identity, family, prejudice, marginalisation and courage.
Keywords: Queer theory; Marginalisation; Characterisation; Sexual identity